Processing the measurements from stationary gravimeters (Proceedings of Voronezh State University. Series: Geology, 2020)
Introduction: The comparison of gravitational waves at research units and observatories located on different continents demonstrated that the vibrations are synchronised. The measurements often vary in the degree of accuracy, which becomes obvious during their processing. In such cases, sampling has to be performed in order for the measurements from different units to have the same sampling interval. Most often, the most accurate measurement is determined, and the rest of the measurements are equated to this one. The same happens when there are too many measurements for computers to process. In this case, the accuracy of measurements can be improved by increasing the sampling interval. It can also be done by selecting individual values within a certain interval, or by calculating the mean interval value. Methodology: Both methods were tested using the measurements of a dual sensor superconducting gravimeter, which allowed the evaluation of both the selection of gravity values and the vertical gravity gradient. We used the dual sensor superconducting gravimeter because at the moment it is one of the most accurate devices. The measurements were performed with a one second sampling interval, which enabled us to manually alter the sampling rate and assess the way its affected the measurements. The initial measurements provided by the device were taken from open sources. Results and discussion: Since averaged interval sampling helps to retain most of the data, we suggest that it should be considered the optimal method for processing the measurements. Simple sampling can be used for qualitative interpretation of the measurements. Conclusions: The experiment demonstrated that the optimal processing method is the averaged interval sampling.
Keywords: lunar-solar gravity variations; non-tidal gravity variations; vertical gravity gradient; meteor showers; pulsations